2019
DOI: 10.1029/2019ja026772
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Precipitation of Relativistic Electron by EMIC Rising‐Tone Emissions Observed by the Van Allen Probes

Abstract: On 23 February 2014, Van Allen Probes sensors observed quite strong electromagnetic ion cyclotron (EMIC) waves in the outer dayside magnetosphere. The maximum amplitude was more than 14 nT, comparable to 7% of the magnitude of the ambient magnetic field. The EMIC waves consisted of a series of coherent rising tone emissions. Rising tones are excited sporadically by energetic protons. At the same time, the probes detected drastic fluctuations in fluxes of MeV electrons. It was found that the electron fluxes dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 49 publications
5
42
0
Order By: Relevance
“…Recent analysis (Kubota et al, ; Shoji & Omura, ) showed that rising tone EMIC emission can produce rapid heating of energetic protons around the equator because of the stable trapping, as well as the atmospheric losses of relativistic electrons inside the plasmasphere. Nakamura et al () presented direct Van Allen Probes observations of an event of rapid precipitation of relativistic electrons in timescale shorter than 1 min and in <1 hr of MLT, possibly through nonlinear trapping by EMIC rising tones. Quantitative assessment of the occurrence rates of EMIC rising tones is required to establish their importance to the ring current and radiation belts.…”
Section: The Role Of Nonlinear Processes In the Global Variability Ofmentioning
confidence: 99%
“…Recent analysis (Kubota et al, ; Shoji & Omura, ) showed that rising tone EMIC emission can produce rapid heating of energetic protons around the equator because of the stable trapping, as well as the atmospheric losses of relativistic electrons inside the plasmasphere. Nakamura et al () presented direct Van Allen Probes observations of an event of rapid precipitation of relativistic electrons in timescale shorter than 1 min and in <1 hr of MLT, possibly through nonlinear trapping by EMIC rising tones. Quantitative assessment of the occurrence rates of EMIC rising tones is required to establish their importance to the ring current and radiation belts.…”
Section: The Role Of Nonlinear Processes In the Global Variability Ofmentioning
confidence: 99%
“…However, on the inbound half of orbit 3214, RBSP‐B observed larger amplitude EMIC waves than RBSP‐A and more rising tones than RBSP‐A. Some studies have suggested that EMIC waves with rising tones are more effective at particle scattering than unstructured EMIC waves (Kubota et al, 2015; Kubota & Omura, 2017; Nakamura et al, 2019). A detailed analysis of the EMIC rising tone triggered emissions observed on 22 December 2015, including wave normal analysis, proton distribution functions, and the rising tone frequency sweep rates, will be covered in a separate paper.…”
Section: Discussionmentioning
confidence: 99%
“…The present study focuses on the effect of the parallel‐propagating monochromatic EMIC waves with a moderate amplitude (3 nT). In fact, extremely large‐amplitude (~10 nT) EMIC waves are observed inside the Earth's inner magnetosphere (e.g., Engebretson et al, 2015; Nakamura et al, 2019). As the amplitude of EMIC waves increases, more electrons, either resonant or nonresonant, are expected to have nonlinear behaviors.…”
Section: Conclusion and Discussionmentioning
confidence: 99%